(3GdMdd GdSfOSjI aj GdCNHGQ GdJhfSjIs - (3eMeO GdhRjQ , eMeO Hf eMeO Hf eUWaj GdCfOdSj, CHh YHO Gddg SQGO GdOjf,J (B1149 (3g` s
(3ChdgG (B:s
(3hHYO , aEfg deG JbOe GdhYO aj UOQ GdLRA GdChd ef gPG GdcJGH HCf fLYd GdLRA GdKGdK efg ai PcQ GdOhdI GdJhfSjI s
(3BNQgG (B:s
(3hYXe hbGQJUHM GdTe Mhdg aQjbjf QGL Yahg hONjd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B66 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B458 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B685 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- - (3U (B154 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs